2018
DOI: 10.3390/ijerph15112359
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Health Interventions in Volcanic Eruptions—Community Wearability Assessment of Respiratory Protection against Volcanic Ash from Mt Sinabung, Indonesia

Abstract: Inhalation of ash can be of great concern for affected communities, during and after volcanic eruptions. Governmental and humanitarian agencies recommend and distribute a variety of respiratory protection (RP), commonly surgical masks but, also, industry-certified N95-style masks. However, there is currently no evidence on how wearable they are within affected populations or how protective wearers perceive them being against volcanic ash (which will influence the likelihood of uptake of recommended interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The aim of the HIVE project was to provide an evidence base on effective respiratory protection against volcanic ash for community use. This evidence base includes not only identifying which types of respiratory protection are effective and wearable [the results of which are published in: 1416] but, also, understanding the factors that influence people's motivation to protect themselves and the actions they take when ash is in the air, including whether or not they wear masks.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of the HIVE project was to provide an evidence base on effective respiratory protection against volcanic ash for community use. This evidence base includes not only identifying which types of respiratory protection are effective and wearable [the results of which are published in: 1416] but, also, understanding the factors that influence people's motivation to protect themselves and the actions they take when ash is in the air, including whether or not they wear masks.…”
Section: Introductionmentioning
confidence: 99%
“…A perception of difficulty in breathing was a factor causing the children to remove facemasks. Previous studies have also found that perceptions of increased breathing resistance reduces the wearability of facemasks in adults [20,27,28]. In this study, for all masks, breathability was one of the lowest rated wearability criteria (i.e., the children perceived the masks to negatively affect their ability to breathe).…”
Section: Discussionmentioning
confidence: 51%
“…To our knowledge, this is the only assessment of comfort of facemasks for children, prior to this study, and it should be noted that the study was commissioned and funded by the manufacturer of the masks. Galea et al (2018) conducted a study with adults in Indonesia, testing the wearability of facemasks used as protection against volcanic ash, including N95 masks and surgical masks [20]. Results highlighted some wearability barriers to the uptake of some facemasks which included perceptions of poor fit, comfort and breathability.…”
Section: Introductionmentioning
confidence: 99%
“…The evidence also indicates that some facemasks are perceived by those who wear them as being more wearable than others, therefore likely affecting uptake. 15,16…”
Section: Facemasksmentioning
confidence: 99%
“…A close-fitting mask (ie, an industrial N95 style mask) may pose additional risks for people with respiratory or cardiac conditions or claustrophobia. 5,15,16 Such information is already available for some types of exposures, such as to volcanic ash. 28 The information needs to be evidence-based so that potential users are not misled about the level of protection that a facemask can or cannot provide.…”
Section: Choice Of Maskmentioning
confidence: 99%